Development of Learning Modules for Entrepreneurship Courses to Train The Independence of Agricultural Product Technology Study Program Students - Utami, Arfiati Ulfa; Setyawan, Bagus; Ulfa, Rosiana (UNDIKMA, 2024)
This research aims to produce a learning module for entrepreneurship courses to train student independence. The module was prepared in the form of a printed module. This module was created as an educational tool for entrepreneurship classes in the Faculty of Agriculture's Agricultural Product Technology Study Program, PGRI Banyuwangi University. The technique employed in developing this module is the ADDIE development model, this model is used because the development stages are simpler and the time used is not too long. The study's findings are in the form of an entrepreneurship learning module to determine the feasibility of using this module, trials have been carried out including individual trials and group trials. The individual trial involved 3 students, while the group involved 9 students. In this study, it was found that the confirmation from material experts was 92.5% and the media expert validation was 87.5% so that it could be categorized as very good. It is also carried out limited and group trials with the aim of seeing the feasibility of the products developed. The restricted trial's outcomes were as follows an average of 89.58%, meaning that the average can be categorized as excellent and the results of the group trial obtained an average of 90.26% so that the developed module is categorized as feasible and can train student independence.